La educación universitaria en el siglo xxi - Medina Flores, Víctor Andrés (2008)
Educacion University in the middle of century XX is affected by new changes that take place in the world due to the development of computer science and of the electronics which together they come revolutionizing the educative processes changing attitudes and conducts generating improvements that they directly involve to both component of the education: professors and students. Century XXI forms a situation much but it jeopardize with the changes and the innovations of the education, the professor and the student must assume the planned change where the information and the technology occupy an important place, being, necessary the continuous and significant learning, to be in agreement with the era of the knowledge